An interesting result can be obtained by the following argument, which is essentially identical to that made above in Ch. 5.1. Let the antenna, terminated by a matched resistor, be surrounded completely by a surface at temperature T. In a state of equilibrium the antenna temperature will be TA = T, while also Tb = T. Substitution in Eq. (5.11) leads to f A(0, f) dW=12, •J 4 p

Thus the full sphere integral of the reception pattern is equal to the wavelength squared. We can write Eq. (5.12) also as

A(0, 0) = l2 / £ g(0, f) dW = l2 / WA = l2 G / 4 p,

where we have made use of Eqs. (5.2 and 5.3). It is easily seen that Eq. (5.13) is identical to Eq. (5.6). This is obvious, because we have used the same argument here as in the discussion leading to Eq. (5.6). We can rewrite Eq. (5.11) as

0 0

Post a comment